Working Families: Age, Gender and Daily Survival in Industrializing Montreal - Bradbury, Bettina (Labour / Le travail, 1994)
issued: 1994-21-00
Keywords: Famille; Femmes

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail

Making and Breaking the Rules. Women in Quebec, 1919-1939 - Lévesque, Andrée (McClelland & Stewart, 1994)
Translators: _:n8836
Keywords: Avortement; Famille; Femmes; Prostitution